Asymmetric Forms of Linguistic Adaptation in Interactions Between Flemish and Dutch Speakers - Swerts, Marc; Van Heteren, Anouk; Nieuwdorp, Chloë; Von Oerthel, Eline; Kloots, Hanne (Frontiers in Communication, 2021)
Conversation partners tend to copy elements of each other’s utterances during a spoken interaction. This article investigates possible asymmetries in this adaptive process. We study game-based dialogues between Flemish and Dutch speakers, who officially speak the same language, but who can differ in their default use of words and in their pronunciation. Our general hypothesis, mainly based on previous studies that focused on long-term forms of adaptation and on previous studies on exchanges between categorical and variable language users, is that Flemish speakers adapt more in interactions towards Dutch speakers, than vice versa. The article describes two experiments using variants of the same experimental paradigm. Experiment 1 investigates lexical adaptation and tests whether Flemish speakers indeed adapt more to Dutch ones than the other way around. Experiment 2 looks at how adaptation of lexical forms relates to adaptation in terms of pronunciation. Both experiments bring to light that Flemish speakers indeed converge more to Dutch ones, than vice versa, especially in terms of choice of lexical forms.